The Influence of Incentives and Organizational Commitment on Job Satisfaction - Kuspriyono, Taat Kuspriyono; Sitohang, Menari; Setiawan, Roy; Munizu, Musran; Wa Ode Nur (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
This study aims to examine the impact of incentives and organizational commitment on job satisfaction at PT ABC in Pekalongan City. A quantitative approach was employed, with data collected through questionnaires. A sample of 90 employees was selected using purposive sampling. Data analysis was performed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) method, supported by SmartPLS version 3.2.9 software. The findings reveal that incentives have a significant positive effect on job satisfaction at PT ABC in Pekalongan City. Similarly, organizational commitment also significantly influences job satisfaction. Furthermore, both incentives and organizational commitment together contribute to job satisfaction at PT ABC in Pekalongan City.